2019
DOI: 10.1103/physrevd.100.043514
|View full text |Cite
|
Sign up to set email alerts
|

Modeling biased tracers at the field level

Abstract: Two major goals of our analysis are to check how well the bias expansion describes the simulated overdensity of dark matter halos, which we will refer to as "true" halo overdensity δ truth h , and to measure the amplitude and the scale dependence of the residual noise. These two questions are tightly related to each other. To illustrate this, let us

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
166
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(173 citation statements)
references
References 114 publications
7
166
0
Order By: Relevance
“…This is supported by the results of Ref. [78]. This study also showed that the amplitude of the shot noise can be super-or sub-Poissonian for very light or massive halos, respectively.…”
Section: )supporting
confidence: 87%
See 1 more Smart Citation
“…This is supported by the results of Ref. [78]. This study also showed that the amplitude of the shot noise can be super-or sub-Poissonian for very light or massive halos, respectively.…”
Section: )supporting
confidence: 87%
“…As for the higher-derivative bias coefficient, the measurements from N-body simulations [34,78,101] suggest that it is an order-one quantity in units of [Mpc/h] 2 . Thus, we adopt the following fiducial value along with the time-dependence that corresponds to the one-loop contribution,…”
Section: Parameter Definition Fiducial Value Hmentioning
confidence: 99%
“…To fit for the bias parameters, we use the approach developed by ref. [23], specifically we match the model with the observations at the level of the field instead of only matching the two-point functions. The component biased fields are 'shifted' to their Eulerian position with the non-linear dynamics of choice and then binned onto the grid with cloud-in-cloud (CIC) interpolation to get the corresponding Eulerian (shifted) fields (δ L (x), ...).…”
Section: Forward Modelmentioning
confidence: 99%
“…where the sum is over half of the k plane since δ (k) = δ(−k) for the Fourier transform of a real field. In principle the bias parameters can be made scale dependent, b(k), and treated as transfer functions [23]. To get these transfer functions, we simply minimize Eq.…”
Section: Forward Modelmentioning
confidence: 99%
“…Nonetheless, clustering and halo exclusion may introduce deviations from a Poissonian shot noise. This non-Poissonian contribution can change the amplitude of the shot noise and even induces a small scale dependence [133,134].…”
Section: Cross-correlation With Galaxy Surveysmentioning
confidence: 99%